2018
DOI: 10.1111/trf.14652
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Ebola virus and Middle East respiratory syndrome coronavirus in platelet concentrates and plasma by ultraviolet C light and methylene blue plus visible light, respectively

Abstract: Both THERAFLEX UV-Platelets (UVC) and THERAFLEX MB-Plasma (MB/light) effectively reduce EBOV and MERS-CoV infectivity in platelets and plasma, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
125
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 32 publications
3
125
0
2
Order By: Relevance
“…The infectious titer of virus did not show any significant reduction after 25 cycles of thawing and freezing [44]. After the outbreak of SARS and MERS, a few studies investigated pathogen inactivation/reduction technologies (PRTs) based on in-house or commercial methods with the aim to decrease or completely eradicate the potential risk of transmission of coronaviruses via blood products or blood derivatives [45][46][47][48][49][50][51][52][53][54]. These studies are summarized in Table 1.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infectious titer of virus did not show any significant reduction after 25 cycles of thawing and freezing [44]. After the outbreak of SARS and MERS, a few studies investigated pathogen inactivation/reduction technologies (PRTs) based on in-house or commercial methods with the aim to decrease or completely eradicate the potential risk of transmission of coronaviruses via blood products or blood derivatives [45][46][47][48][49][50][51][52][53][54]. These studies are summarized in Table 1.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
“…Illumination with different wavelengths also influenced activities of SARS and MERS virus in blood. Ultraviolet (UV)-A [46,47,51]and UV-B light [54] in the presence of amotosalen or riboflavin could inactivate the pathogens' nucleic acids, whereas a third PRT method uses UV-C light only [45,48]. These commercial systems could reduce the activities of SARS and MERS virus in plasma or platelet concentrates to different degrees.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
“…It has been demonstrated that UVC treatment significantly reduces the infectivity of platelet products contaminated by disease‐causing bacteria, viruses, and protozoa. In addition, THERAFLEX UV‐Platelets inactivates contaminating donor WBCs while preserving platelet function and coagulation factors …”
mentioning
confidence: 99%
“… The UVC transparency of the irradiation bags was increased during the development of the THERAFLEX UV‐Platelets system. The inactivation efficacy of a UVC dose of 0.2 J/cm 2 used as full dose in this study and other recent studies , is equivalent to a UVC dose of 0.3 J/cm 2 used in the early phase of development , …”
Section: Discussionmentioning
confidence: 51%